2007
DOI: 10.1158/1055-9965.epi-07-0611
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Blood, Saliva, and Buccal Cell Samples in a Pilot Study on the Danish Nurse Cohort: Comparison of the Response Rate and Quality of Genomic DNA

Abstract: In this study, we compared the response rates of blood, saliva, and buccal cell samples in a pilot study on the Danish nurse cohort and examined the quantity and quality of the purified genomic DNA. Our data show that only 31% of the requested participants delivered a blood sample, whereas 72%, 80%, and 76% delivered a saliva sample, buccal cell sample via mouth swabs, or buccal cell sample on FTA card, respectively. Analysis of purified genomic DNA by NanoDrop and agarose gel electrophoresis revealed that blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
192
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(211 citation statements)
references
References 11 publications
12
192
3
4
Order By: Relevance
“…The overwhelming majority (4584 out of 4678 or 98%) of samples provided DNA of sufficiently high yield and quality (Table 3) for multiple genotyping assays as evidenced by the high genotyping success rates for both DNA collection methods ( Table 4). The DNA yield differed between the two collection methods, with whole saliva yields being higher than yields from sponges (Table 3) and this is in line with previous reports in the literature (1,2,4,5,(14)(15)(16)(19)(20)(21). Total DNA yield from the 4 ml Oragene DNA/saliva solution fulfilled, on average, the specifications of the manufacturer of above 20 µg (22) for the whole saliva collection method (Table 3).…”
Section: Discussionsupporting
confidence: 86%
“…The overwhelming majority (4584 out of 4678 or 98%) of samples provided DNA of sufficiently high yield and quality (Table 3) for multiple genotyping assays as evidenced by the high genotyping success rates for both DNA collection methods ( Table 4). The DNA yield differed between the two collection methods, with whole saliva yields being higher than yields from sponges (Table 3) and this is in line with previous reports in the literature (1,2,4,5,(14)(15)(16)(19)(20)(21). Total DNA yield from the 4 ml Oragene DNA/saliva solution fulfilled, on average, the specifications of the manufacturer of above 20 µg (22) for the whole saliva collection method (Table 3).…”
Section: Discussionsupporting
confidence: 86%
“…This offered those with a fear of needles or seeing blood the opportunity to avoid doing something they disliked. Other studies find participation is higher for less invasive DNA collection options (e.g., saliva or buccal) than those asked to donate a blood sample in population studies (Hansen et al 2007;Johnson et al 2011); saliva return rates often vary between 52-80 % (Etter et al 1998(Etter et al , 2005Nishita et al 2009). Second, providing an incentive also increased the chance of obtaining a biologic sample.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the decline in our interview rate include factors commonly associated with attrition in a longitudinal study of a cohort being followed over time, environmental influences (e.g., societal views regarding greater privacy), and perhaps the procedure change as this was the first time the interview also had a genetic component (Banks et al 2012;Matsui et al 2005). Studies have found that response rates to questionnaires decrease when the study also includes a DNA component (Matsui et al 2005;McQuillan et al 2006;Melas et al 2010), although those who participate are willing to donate biologic samples for DNA testing (Hansen et al 2007). DNA collection experiences may be different when offered after longstanding participation, and these results may not generalize to samples where DNA sampling is offered from the outset.…”
Section: Discussionmentioning
confidence: 99%
“…Dentists are well-positioned to collect these buccal cells by simply scratching the inside of the patient's cheek with a cytology brush. Theoretically, the easiest, fastest, most non-invasive and painless method for the collection of test materials from humans will lead to a larger amount of individuals agreeing to participate in studies for this purpose, since a significantly smaller number of individuals agree to donate when blood samples are required (Hansen et al 2007). Accordingly, it is assumed that novel mutations associated with tooth agenesis will be found in the coming years, substantially increasing our understanding regarding its genetic etiology.…”
Section: Mutations Associated With Tooth Agenesis and How This Knowlementioning
confidence: 99%